การพัฒนาเครื่องมือทางแสงสำหรับวัดอุณหภูมิเจลาติไนเซซันของสตาร์ชและผลของบอลล์มิลล์ต่อุณหภูมิเจลาติไนเซชัน - กรวิกา ฉิมโฉม (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objectives of this thesis were to produce an optical tool for determination of starch gelatinization temperatures and study effect of ball milling on gelatinization temperatures. The optical tool was developed based on the concept from Kofler hot stage microscope that counting the number of starch granules lost their birefringence when gelatinized; but it was developed to be less depending on operators by using a photoelement for detecting intensity of light pass through starch suspension. This tool comprised of light source made from light emitting diode (LED) and electronic circuit for measuring temperature and light intensity. Initial gelatinization temperatures of potato and tapioca starches which were measured at 98% intensity of light by this tool were 58.6±1.1 and 60.8±0.8 ℃, respectively. However, it still requires some improvement in the electronic circuit for measuring the light intensity of small size starch granules such as tapioca starch. Effect of ball milling time (0.12hr) on properties of potato and tapioca starches were studied. Increasing the milling time, surface of both starch granules were rougher, granules lost more birefringence and their degree of crystallinity decreased. Other properties such as % starch damage, water absorption at room temperature, swelling power and % solubility at temperature 55 ℃ increased significantly (p≤0.05). Pasting properties of the starches from Brabender viscograph and Rapid visco analyser (RVA) were changed. Differential scanning calorimetry (DSC) studies highlighted changes effect by milling time in the gelatinization behavior of both starches samples significantly (p≤0.05). Moreover, gelatinization temperatures of both starches measured by the optical tool decreased significantly (p≤0.05) as ball milling time increased. Comparison of the initial gelatinization temperatures measured by the four instruments founded that temperatures measured by DSC was the lowest and closest to the optical tool, follow by Brabender viscograph, and RVA gave the highest initial temperatures of each starch. Linear correlation coefficients (r) of the gelatinization temperature data from these four equipments were higher than 0.8